ROTATIONAL AND VIBRATIONAL-ROTATIONAL RELAXATION IN COLLISIONS OF CO2(0110) WITH HE ATOMS - Clary, D (1983)
Rotational and vibrational-rotational relaxation of CO2(01 10) in collisions with He atoms is studied theoretically. Cross sections and rate coefficients have been calculated using a vibrational close-coupling, rotational infinite-order sudden method, together with an ab initio potential energy surface. Comparisons with previous calculations and experiments on rotational relaxation in He+CO2(0001) are made. The rotational relaxation cross sections are found to be insensitive to the vibrational dependence of the He-CO2 potential. Transitions between even and odd rotational states of the (0110) level have relatively small cross sections. Interesting oscillating structures are predicted for the rotational dependence of the cross section distributions for transitions involving the (0110) level. © 1983 American Institute of Physics.